Biomarkers study in rainbow trout exposed to industrially contaminated groundwater - Nadjet Benchalgo; François Gagné; Michel Fournier (MDPI AG, 2014)
The spill of liquid industrial waste from chemical and petrochemical industries in Mercier lagoons located 20 km south of Montreal, Quebec, caused a major groundwater contamination by industrial contaminants. The aim of this study was to investigate the toxic effects of Mercier groundwater, following 4 and 14 days of exposure to graded concentrations from three wells at increasing distances 1.2, 2.7 and 5.4 km from the source of contamination. Rainbow trout were examined for several biomarkers of defense [ethoxyresorufin O-deethylase (EROD) and gluthatione S-transferase (GST) activities] and those of tissue damage [lipid peroxidation (LPO) and DNA strand breaks]. The results showed that EROD activity was significantly enhanced in hepatic tissue at 1.2 and 5.4 km, whereas inhibition in activity was observed in group at 2.7 km. Therefore, GST activity was significantly increased at 3.1% concentration for the 2.7 km well. No change in LPO was observed. However, a significant induction of DNA strand breaks in liver was obtained at each distance. In conclusion, the data suggest that the release of these contaminants in groundwater leads to increased biotransformation for coplanar aromatic hydrocarbons and DNA damage in groundwater.